Alinov M., Skakova А.А., Тastambek K.Т. Factors of ecology synergy from EXPO-2017: Казахский национальный университет имени аль-Фараби, Казахстан, г. Алматы 2НИИ проблем экологии, Казахстан, г. Алматы *e-mail: amxeconom@mail.ru (Eurasian Journal of Ecology, 2018)
In the review article, the results and synergetic effect for the sphere of ecology of Kazakhstan ofthe last international exhibition EXPO-2017 «Energy of the future» are considered. The significance andinternational scope of EXPO are confirmed by the participation of 115 countries and more than 20international organizations and demonstration of 193 advanced technologies from around the world.Most of the projects devoted to green energy technologies, one way or another were involved in theenvironmental impact of emissions of traditional hydrocarbon energy. To obtain a better effect, theanalysis results are structured according to seven factors influencing the environment: global and international; ecology and ecological safety; the energy of the future; innovative technologies; investmentand business; development of ecology of regions; science and education. The generalized factors offoreign practice in solving modern environmental problems, according to the authors, will give newimpetus to scientific and technical research in Kazakhstan. First of all, important are the foreign projectspresented at the EXPO related to the reduction of greenhouse gases as a result of replacing hydrocarbonenergy with renewable energy sources and energy efficient technologies in a wide range of industriesand economies. Among the best practices are innovative technologies for green energy, new materials,organic agriculture, waste recycling and recycling, and the purification of natural resources. At the endof the EXPO, 170 projects of various countries were selected by a special expert commission, which willbe further applied in practice in various sectors of production and business, as well as in science andeducation.Keywords. EXPO-2017, ecology, synergy, energy of the future, green technologies, scienceand educationKey words: EXPO-2017, ecology, synergy, energy of the future, green technologies, science andeducation.